1979
DOI: 10.1111/j.1398-9995.1979.tb04375.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Smear as a Screening Test for Immediate‐Type Nasal Allergy

Abstract: From a previous sample of634 students and school children, 115 subjects were selected for a thorough rhinological examination and allergy work-up in order to assess the value of nasal secretion eosinophilia in screening for immediate-type nasal allergy, Part of the subjects had, in the previous study, been found to have secretion eosinophilia and a history of chronic/allergic rhinitis, part of the subjects had either a secretion eosinophilia or a rhinitis history, and part of them had neither a secretion eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…857 Many studies have shown a high correlation of nasal eosinophilia and allergic rhinitis; however, it is questionable how much this benefits the clinician in making the diagnosis of allergic rhinitis. [87][88][89] In a study of adolescents and adults, adding nasal smears for eosinophils to an expert's clinical evaluation in establishing a diagnosis of allergic rhinitis contributed very little to the final diagnosis and was considered clinically irrelevant. 90 When eosinophils in nasal smears are present, there is only a 71% correlation with SPTs and a 69% correlation with nasal challenge tests, suggesting that routine use of the nasal smear may not be beneficial.…”
Section: Nasal Provocation Testingmentioning
confidence: 98%
See 1 more Smart Citation
“…857 Many studies have shown a high correlation of nasal eosinophilia and allergic rhinitis; however, it is questionable how much this benefits the clinician in making the diagnosis of allergic rhinitis. [87][88][89] In a study of adolescents and adults, adding nasal smears for eosinophils to an expert's clinical evaluation in establishing a diagnosis of allergic rhinitis contributed very little to the final diagnosis and was considered clinically irrelevant. 90 When eosinophils in nasal smears are present, there is only a 71% correlation with SPTs and a 69% correlation with nasal challenge tests, suggesting that routine use of the nasal smear may not be beneficial.…”
Section: Nasal Provocation Testingmentioning
confidence: 98%
“…Although nasal cytology may be useful in differentiating infectious from noninfectious nasal and/or sinus disease, the clinical value, particularly for the diagnosis of allergic rhinitis, is limited by low specificity and sensitivity. [87][88][89][90][91] For example, neutrophils may be present not only in acute and chronic sinusitis but also in conjunction with eosinophils in patients with allergic rhinitis who also have an acute infection process. 92 Cultures of the nasopharynx without visualization in children with rhinitis is of no value because pathogenic bacteria, as part of the normal flora, have been recovered in as many as 92% of asymptomatic healthy children.…”
Section: Executive Summary Definition Of Rhinitis [Summary Statement 1]mentioning
confidence: 99%
“…20 Malmberg and Holopainen demonstrated the correlation between nasal eosinophilia and allergic rhinitis. 21 Relationship between allergic rhinitis and nasal eosinophilia has been also studied by Kajosaari and Saarinen. In this survey, a group of 178 patients with allergic rhinitis was observed; the presence of eosinophils and mast cells in cytograms obtained from the nasal mucosa (using nasal smear taken by wiping the mucosa with a cotton-tipped applicator) was an important indicator of allergic rhinitis, characterized by a high specificity but a low sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years nasal cytology is increasingly used in the study of either allergic and vasomotor rhinological disorders, or infectious and inflammatory rhinitis [1,2]. Since nasal cytology can detect cellular changes of epithelium exposed to physical-chemical inflammation [3,4], acute or chronic infections of different nature (viral, bacterial, fungal or parasitic) [5,6], it has been matter of interest, both in basic and clinical research.…”
Section: Introductionmentioning
confidence: 99%